Journal of the convention of the people of the state of Delaware : which assembled at Dover, in the year of our Lord, one thousand eight hundred and thirty-one, and of the independence of the United States, the fifty-sixth ([R. & J.B. Porter, printers], 1831)
1831 Journal of the Convention of Delaware held in Dover to make any necessary amendments to the state constitution. Included were an amended constitution (page 81) and an index.